2018
DOI: 10.1111/cod.12945
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkeratotic hand eczema compared to other subgroups of hand eczema – a retrospective study with a follow‐up questionnaire

Abstract: Studies evaluating the subdiagnoses of hand eczema are needed, to further validate the classification system, and to provide more detailed information about demographic factors, severity and possible risk factors for different subgroups of hand eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…For ACD, there may be an overlap between working life and leisure time regarding exposure to allergens such as biocides and fragrances. 50 There appears to be no difference in skin barrier susceptibility or stratum corneum lipids between hyperkeratotic HE and ICD/ACD on the hands. 34 Protein contact dermatitis is often caused by natural rubber latex gloves, although the number of patients clinically allergic to natural rubber latex has been significantly declining 45 or by exposure to foods.…”
Section: Occupational Hementioning
confidence: 92%
See 1 more Smart Citation
“…For ACD, there may be an overlap between working life and leisure time regarding exposure to allergens such as biocides and fragrances. 50 There appears to be no difference in skin barrier susceptibility or stratum corneum lipids between hyperkeratotic HE and ICD/ACD on the hands. 34 Protein contact dermatitis is often caused by natural rubber latex gloves, although the number of patients clinically allergic to natural rubber latex has been significantly declining 45 or by exposure to foods.…”
Section: Occupational Hementioning
confidence: 92%
“…48 It is more often combined with eczema on the feet than other sub-diagnoses, 49 occurs more frequently in males; tobacco smoking is more frequent among patients with hyperkeratotic HE, and the eczema is often severe requiring systemic treatment. 50 There appears to be no difference in skin barrier susceptibility or stratum corneum lipids between hyperkeratotic HE and ICD/ACD on the hands. 51 The sub-diagnosis of acute recurrent vesicular HE is not very well understood.…”
Section: Classificationmentioning
confidence: 92%
“…132 Hyperkeratotic HE is not attributable to the other categories, it is more common in men than in women, and an association with tobacco smoking has been indicated that seems to be stronger than for the other subtypes. 135,136 Acute recurrent vesicular HE (previously called dyshidrotic endogenous eczema or pompholyx) has been described as a separate entity in most proposed classifications, 25,126,132 and poses challenges with regard to diagnosis and treatment. The term acute recurrent vesicular HE describes the clinical course and morphology but not the aetiology and may, therefore, be observed in the context of several aetiologies.…”
Section: Scrutiny Of Ingredient Labels and Safety Data Sheetsmentioning
confidence: 99%
“…If there was no response, a reminder was sent up to two times. The questionnaire covered the following items: atopy, patch testing, QoL, improvement/deterioration of HE, educational level, current occupational status and knowledge of skin protection, 21 and whether they had actually participated in the guided talk. Information on atopic dermatitis was assessed with a validated question on previous or current atopic dermatitis, 22 and a question on whether the patients had one or more positive patch test reactions was also included, as well as the DLQI questionnaire.…”
Section: Methodsmentioning
confidence: 99%